Application technology of SfMNPV-6nd in the control of fall armyworm - Joáz Dorneles Junior; Carlos Gilberto Raetano; Evandro Pereira Prado; Regiane Cristina de Oliveira (Pesquisa Agropecuária Brasileira, 2022)
Abstract The objective of this work was to evaluate the application technology and the compatibility of the SfMNPV-6nd baculovirus with surfactants and markers in the mortality of Spodoptera frugiperda second-instar larvae. The compatibility studies were carried out with the brilliant blue (BB) dye and copper oxychloride (CO) markers and with the polyalkylene oxide heptamethyltrisiloxane (PH) and ethoxylated alkylphenol (EA) surfactants mixed with the SfMNPV-6nd biological insecticide. Droplet dispersion was assessed by spraying a SfMNPV-6nd solution on corn plants using flat fan and hollow cone nozzles. The evaluated parameters were: spray deposits, volumetric median diameter (VMD), droplet size, pH of spray solution, and mortality of second-instar S. frugiperda larvae. The PH and EA surfactants present synergism with SfMNPV-6nd and increase S. frugiperda control. The addition of the EA and CO surfactants to the SfMNPV-6nd solution reduces pH values. Droplet density, VMD, spray deposition of the SfMNPV-6nd solution, and mortality of S. frugiperda second-instar larvae do not differ among treatments regardless of the type of nozzle used.